Incidencia de la pandemia en la liquidez de la Cooperativa de Ahorro y Crédito San Antonio Ltda. Vinces en el año 2020 - Arévalo Velásquez, Suanny Anahi (2021)
This case study is aimed at analyzing the incidence of the pandemic on liquidity in the San Antonio Ltda.-Vinces savings and credit cooperative and at an event that caused variations at a general level in the different economic sectors. The San Antonio Credit Union Ltda.- Vinces is an entity that offers services and products for the benefit of members and interest groups, in order to improve the quality of life through competitive financial services, since they integrate values such as transparency , ethics, respect, leadership among others, which play a key role in the social economy, the same one that aims to achieve social equity and equality, with partners and stakeholders. The analysis of the liquids within the institutions is very important since it helps us to maintain an efficient control of the profitability or solvency that the evaluated institution has, that is why the analyzes are used to show whether the effects by pandemic are positive or negative, and if they represent a representative variation for the cooperative's activity. The methodology that is implemented is that of the inductive and deductive method since through the deductive method the interview was carried out to learn about the situation of the company during the contingency that occurred worldwide, and deductive because after analyzing the situations presented, allow us to reach conclusions on the case.